2016
DOI: 10.1371/journal.pone.0165599
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tool to Stage Households’ Readiness to Change Dietary Behaviours in Kerala, India

Abstract: Dietary interventions and existing health behaviour theories are centred on individuals; therefore, none of the available tools are applicable to households for changing dietary behaviour. The objective of this pilot study was to develop a practical tool that could be administered by community volunteers to stage households in rural Kerala based on readiness to change dietary behaviour. Such a staging tool, comprising a questionnaire and its algorithm, focusing five dietary components (fruits, vegetables, salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As there was no tool till date to assess the stage of change at a household level as opposed to an individual level; key findings related to food decisions [ 36 ] and the conceptual model [ 26 ] were used to develop such a tool that could be administered by lay community volunteers. This staging tool used a simple algorithm to compute the household stage based on responses from the female heads of households [ 37 ] and, consequently, the tool was administered only to the female heads of the households in this pragmatic RCT. Efficacy and perceived cooperation at the household level were found to be crucial identifiers when assessing the household’s readiness to change dietary behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As there was no tool till date to assess the stage of change at a household level as opposed to an individual level; key findings related to food decisions [ 36 ] and the conceptual model [ 26 ] were used to develop such a tool that could be administered by lay community volunteers. This staging tool used a simple algorithm to compute the household stage based on responses from the female heads of households [ 37 ] and, consequently, the tool was administered only to the female heads of the households in this pragmatic RCT. Efficacy and perceived cooperation at the household level were found to be crucial identifiers when assessing the household’s readiness to change dietary behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Efficacy and perceived cooperation at the household level were found to be crucial identifiers when assessing the household’s readiness to change dietary behaviour. A pilot validation of the tool was carried out before its use in the cRCT [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A systematic review found high prevalence of NCD risk factors in Kerala mostly due to unhealthy dietary patterns and sedentary lifestyle. 7 A 10-year prospective study done in Kerala reports a high incidence of prediabetes showing an epidemic trend towards the development of type 2 diabetes mellitus and that it requires immediate public health action. 8 Bijumone S et al Int J Community Med Public Health.…”
Section: Introductionmentioning
confidence: 99%